Covid-19 Pandemic Publication During 2020 in Indonesia (A Bibliometrics Study) - Trysnawati, Ayu; Allo, Karmila Pare (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
The Covid-19 was declared as a pandemic outbreak by WHO at the beginning of this year. In Indonesia, the government officially stated that the Covid-19 had entered the country was in March 2020. Since then, this outbreak has become an issue that has been widely studied in various disciplines. This research describes the trend of journal publication on the covid-19 pandemic in Indonesia; authors collaboration, publication form, and distribution of disciplines. The data were obtained through GARUDA (Garba Rujukan Digital/Digital Reference Site) published from March to the end of October 2020, where there were 326 journal publications with the theme of the Covid-19 pandemic. With Ms. Excel, the data were analyzed using simple statistics. The results found that there was a total of 688 authors, both individual or collaborative authors from 326 journal publications. The author collaboration rate was 0.561 or 56.1%. It indicates that there were more collaborative articles than written individually. Many forms of publication were research articles compared to literature reviews on the theme of the Covid-19 pandemic. The discipline fields of science that most published the Covid-19 pandemic theme were education, law, and health.